Assessment of bioelectrical impedance analysis in patients with chronic pancreatitis and chronic obstructive pulmonary disease considering exocrine pancreatic insufficiency - Lazaruk, T.; Fediv, O. (Journal of Education, Health and Sport, 2021)
The article describes and analyzes the results of bioelectrical impedance analysis in patients with chronic pancreatitis and chronic obstructive pulmonary disease considering the level of fecal elastase-1. The aim of our study was to investigate the features of Bioelectrical impedance analysis in patients with chronic pancreatitis (CP) and chronic obstructive pulmonary disease (COPD) considering the level of fecal elastase-1. Materials and methods. We examined 84 patients: 30 patients with CP and 54 patients with comorbid pathology - CP and COPD aged 30-65 years (52.36 ± 1.83 years). Patients were hospitalized in the gastroenterology department of theRegionalClinicalHospital,Chernivtsy,Ukraine with exacerbation of CP. COPD was in stable or unstable remission. Fecal elastase-1 level was determined by using the Pancreatic Elastase ELISA (BIOSERV Diagnostics). Biometric measurements were performed with a body composition analyzer BC-601 (TANITA,Japan). All examined patients were divided into groups depending on the exocrine pancreatic insufficiency (EPI): severe (n=9), moderate (n=34), mild (n=23) and normal (n=18). Results. The group of patients with severe EPI was characterized by weight loss. It can be explained by the appearance of absorption disorders of nutrients (malabsorption and maldigestion syndromes). In the groups of moderate and mild EPI fat and cell mass were significantly lower than normal rate in control group. There is a positive correlation between fecal elastase-1 and the level of patients’ metabolism (p<0,05). Conclusions. Bioelectrical impedance analysis (percentage of fat mass, visceral fat level and muscle mass) correlates with the level of fecal elastase-1, which can be used as an additional criteria for the severity of CP and for the control of the effectiveness of substitution therapy.